Soil N-oxide emissions decrease from intensive greenhouse vegetable fields by substituting synthetic N fertilizer with organic and bio-organic fertilizers - Geng, Yajun; Wang, Jinyang; Sun, Zhirong; Ji, Cheng; Huang, Mengyuan; Zhang, Yihe; Xu, Pinshang; Li, Shuqing; Pawlett, Mark; Zou, Jianwen (Elsevier, 2020)
In order to reduce soil and environmental quality degradation associated with the use of synthetic nitrogen (N), substituting chemical fertilizer with organic or bio-organic fertilizer has become an increasingly popular option. However, components of this fertilizer strategy related to mitigation of soil N-oxide emissions and maintenance of crop yield remain uncertain. Here, we evaluated the effects of three different fertilizer strategies, with equal amounts of N, on nitrous oxide (N2O) and nitric oxide (NO) emissions, vegetable yield, and yield-scaled N2O and NO emissions under three consecutive cucumber growing seasons. The three treatments were chemical fertilizer (NPK, urea), organic fertilizer (O, composted cattle manure), and bio-organic fertilizer (O + T, O combined with Trichoderma.spp). Results showed that the NPK plot had the highest area-scaled emissions of N2O (13.1 ± 0.48 kg N ha−1 yr−1) and NO (5.01 ± 0.34 kg N ha−1 yr−1), which were 1.3–1.4 and 3.1–3.7 times greater than the O and O + T plots, respectively. The annual direct emission factors for N2O and NO were 2.08% and 0.92% for the NPK plot, which declined to 1.34% and 0.09% in the O plot, and 1.12% and 0.03% in the O + T plot, respectively. The annual vegetable yield was 117 ± 2.9 t ha−1 for NPK plot and 122 ± 2.0 t ha−1 for O + T plot, which was higher than 111 ± 1.7 t ha−1 for O plot. The yield-scaled N2O + NO emissions differed significantly with fertilization treatment, with the lowest value observed in the O + T plot. We attributed the lower soil N-oxide emissions following organic fertilizer application to the slow release of available N and enhanced denitrification caused by the increase of soil dissolved organic carbon and pH. Compared with the use of organic fertilizer alone, the addition of Trichoderma.spp significantly increased the potential denitrification rate but decreased N2O emissions, which may have promoted the reduction of N2O to N2. Therefore, our results suggest that adopting composted organic fertilizer mixtures with microbial inoculants could be a win-win practice to mitigate gaseous N losses and simultaneously improve crop yield in intensively managed vegetable cropping systems.
Keywords: Nitrous oxide; Nitric oxide; Static chamber technique; Trichoderma; Emission factor; Drip irrigation